Synthesis and Pharmacological Evaluation of (Indol-3-yl)alkylamides as Potent Analgesic Agents - Fouchard, Fabienne; Marchand, Pascal; Baut, Guillaume Le; Emig, Peter; Nickel, Bernd (Arzneimittelforschung, 2001)
A series of (indol-3-yl)alkylamides was synthesized and evaluated for analgesic activity. Two N-(pyridin-4-yl)acetamides, compounds 24 and 25, bearing benzyl or 4-fluorobenzyl moieties in 1-position of indole ring exhibited promising analgesic properties (ED50 = 8.1 and 11 mg/kg p.o., respectively), being as potent as the reference drugs flupirtine (CAS 56995-20-1), ibuprofen (CAS 15687-27-1) and diclofenac (CAS 15307-86-5). The two test compounds were tested for their anti-inflammatory activity by carrageenin-induced edema in rat paw test. 4-Fluorobenzyl derivative 25 whose ID50 was 0.085 ± 0.021 mmol/kg was selected as a lead compound for further pharmacomodulation.
Keywords: Analgesics; Anti-inflammatories; N-(1-Benzyl-1,2,5,6-tetrahydropyridyl) -(indol-3-yl) alkylamides; N-(Piperidin-4-yl)-(indol-3-yl) alkylamides; N-Pyridyl- (indol-3-yl) acetamides, propionamides and butyramides